BlackBerry Curve Made Simple For the BlackBerry Curve 8520, 8530 and 8500 Series - Trautschold, Martin; Mazo, Gary.; Anglin, Steve; Markham, James; Andres, Clay.; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; et al. (Berkeley, CA : Apress, 2010)
You$1 (Bre a proud owner of the bestselling smartphone in the world. Now learn how to make use of all of the Curve$1 (Bs features with this easy-to-read guide from two of the best BlackBerry trainers in the business. BlackBerry Curve Made Simple teaches you how to get the most out of your BlackBerry Curve 8500 and Curve 3G 9300 series smartphone. You$1 (Bll explore all of the features and uncover time-saving techniques$1 (Bfrom emailing and scheduling to GPS mapping and using apps$1 (Ball through easy-to-read instructions and detailed visuals. Written by two successful BlackBerry trainers and authors, this is simply the most comprehensive and clear guidebook to the BlackBerry Curve smartphones available.s
Quick Start Guide -- Getting Around Quickly -- Congratulations on Your BlackBerry Curve! -- You and Your Blackberry Curve -- E-mail Set Up -- Windows PC Setup -- Windows PC Media and File Transfer -- Apple Mac Setup -- Apple Mac Media and File Transfer -- Typing, Spelling, and Help -- Save Time with AutoText -- Personalize Your BlackBerry -- Sounds: Ring and Vibrate -- Phone and Voice Dialing -- Advanced Phone -- E-mail Like a Pro -- Advanced E-mail Topics -- Your Contact List -- Managing Your Calendar -- Getting Tasks Done -- MemoPad: Using Sticky Notes -- SMS Text and MMS Messaging -- Even More Messaging -- Adding Memory with a Media Card -- Exploring Your Music Player -- Snapping Pictures -- Fun with Videos -- Social Networking -- Connect With Wi-Fi -- BlackBerry App World -- Connect with Bluetooth -- Connect as Tethered Modem -- Web Browser -- Add or Remove Apps -- Traveling: Maps and More -- Other Applications -- Searching for Lost Stuff -- Securing Your Data -- Fixing Problems -- More Resources -- Hotkeys $1 (BOpen Almost any App with One Key!.s
Keywords: Computer science; Computer Science; Computer Science, general